Historical Memory in Post-communist Europe and the Rule of Law: An Introduction - Baranowska, Grazyna; Castellanos-Jankiewicz, León (European Papers: A Journal on Law and Integration, 2020)
The legal governance of historical memory in Eastern and Central Europe has grown exponentially over the past two decades. This development runs parallel to the region's reckoning with its communist legacies at the national level, where national identity has been harnessed and sometimes instrumentalised to adopt revisionist interpretations of the past. Mnemonic governance in these States has also been heavily influenced by their proximity or membership to the European Union, which upholds the rule of law as a fundamental value. At the same time, the region's Soviet legacies have been projected by a newfound Russian assertiveness in the area, which has resulted in a phenomena known as memory wars. Those developments are accompanying the ongoing process of democratic transition in Eastern and Central European States. This introductory Article sets out the premises of the Special Section on historical memory in post-Communist Europe and the rule of law, by showing that these democratization processes are far from linear. It does so by first outlining the trajectory of memory governance in Western Europe, which has focused on the Holocaust as a foundational European narrative. It then outlines the tensions emerging between this account and the historical specificities of post-communist States which experienced different forms of totalitarianism. Finally, the introduction shows that the embrace of the rule of law
CRIS-Team Scopus Importer:2024-08-12